2019
DOI: 10.1021/acsapm.8b00219
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Assembly Modulated by Host–Guest Binding

Abstract: A strategy has been devised for improving the quality of polyelectrolyte multilayers formed via the layer-by-layer technique. This strategy involves host−guest complexation of the pendant ions of a polyelectrolyte to reduce their affinity toward the pendant ions of a complementary polyelectrolyte. Evidence for the effectiveness of this approach has been obtained on the basis of film thickness, permeability, and surface roughness measurements of polyelectrolyte multilayers derived from poly(sodium 4-styrenesulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…When one bilayer of PSS/PDDA is deposited onto 30-μm-thick PTMSP that has been surface treated with branched poly(ethylenimine), the permeances of H 2 , CO 2 , and N 2 are only slightly lower than those measured in the absence of this bilayer ( Table 1 ). 16 While a slight increase in the H 2 /N 2 selectivity is apparent, the CO 2 /N 2 selectivity is essentially unchanged. The incremental addition of PSS/PDDA bilayers then leads to a steady decrease in permeance and a corresponding increase in permeation selectivity.…”
Section: Two Recent Developmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…When one bilayer of PSS/PDDA is deposited onto 30-μm-thick PTMSP that has been surface treated with branched poly(ethylenimine), the permeances of H 2 , CO 2 , and N 2 are only slightly lower than those measured in the absence of this bilayer ( Table 1 ). 16 While a slight increase in the H 2 /N 2 selectivity is apparent, the CO 2 /N 2 selectivity is essentially unchanged. The incremental addition of PSS/PDDA bilayers then leads to a steady decrease in permeance and a corresponding increase in permeation selectivity.…”
Section: Two Recent Developmentsmentioning
confidence: 98%
“…A consequence of such defects can be seen from the permeation properties of hyperthin PEMs that have been made from two of the most commonly used polyelectrolytes, i.e., poly(sodium 4-styrenesulfonate) (PSS) and poly(diallyldimethylammonium chloride) (PDDA). 16 …”
Section: Two Recent Developmentsmentioning
confidence: 99%
“…To test this concept, we fabricated polyelectrolyte multilayers using PSS and PDDA as the polyelectrolytes and β‐cyclodextrin (βCD) as the host molecule . Previously, it was shown that βCD acts as an effective host molecule for the aromatic moieties in PSS.…”
Section: Hyperthin Polyelectrolyte Multilayers For Gas Separationsmentioning
confidence: 99%
“…To test this concept, we fabricated polyelectrolyte multilayers using PSS and PDDA as the polyelectrolytes and βcyclodextrin (βCD) as the host molecule. [49] Previously, it was shown that βCD acts as an effective host molecule for the aromatic moieties in PSS. [50] Thus, we fabricated PEMs using aqueous solutions of PSS-βCD and PDDA and compared them with analogous membranes made in the absence of βCD.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…The layer-by-layer (LbL) deposition method is now widely used to synthesize polyelectrolyte multilayers (PEMs) that are of theoretical as well as practical interest. Our own interest in PEMs stems from their possible use as membranes for the separation of gases, especially CO 2 from N 2 , which are the major components of flue gas. Because the flux of a gas across a membrane is inversely proportional to the membrane’s thickness, we have been keenly interested in creating the thinnest PEMs possible, having CO 2 /N 2 selectivities that are potentially exploitable, i.e., single polyelectrolyte bilayers having selectivities >20 and the highest permeability possible with respect to CO 2 …”
Section: Introductionmentioning
confidence: 99%